Platelet lysate-loaded photo-crosslinkable hyaluronic acid hydrogels for periodontal endogenous regenerative technology - Babo, Pedro Miguel Sousa (2017)
The integrity and function of the periodontium can be compromised by traumatic injuries or periodontitis. Currently available clinical therapies are able to stop the progression of periodontitis and allow the healing of periodontal tissue. However, an optimal strategy capable of restoring the anatomy and functionality of the lost periodontal tissue is still to be achieved. Herein is proposed the development of an injectable hydrogel system able to release a growth factors and cells to the periodontal defect. This injectable system is based on a photocrosslinkable hydrogel, prepared from methacrylated hyaluronic acid (me-HA) and incorporating platelet lysate (PL). The delivery of growth factors and cells in situ is expected to enhance regeneration of the periodontium. Various formulations of me-HA containing increasing PL concentrations were studied for achieving the formation of stable photocrosslinkable hydrogels. The produced hydrogels were subsequently characterized to assess mechanical properties, degradation, protein/growth factor release profile, antimicrobial activity and response toward human Periodontal Ligament fibroblasts (hPDLFs). The results demonstrated that it was possible to obtain stable photocrosslinkable hydrogels incorporating different amounts of PL that can be released in a sustained manner. Furthermore, the incorporation of PL improved (p < 0.02) the viscoelastic properties of the hydrogels and enhanced their resilience to the degradation by hyaluronidase (HAase). Additionally, the PL was shown to provide antimicrobial properties. Finally, hPDLFs, either seeded or encapsulated into the developed hydrogels, showed enhanced proliferation over time (p < 0.05), proportionally to the increasing amounts of PL present in the hydrogel formulations.